Engagement in linkage to mental health care program in the Rockaways after Hurricane Sandy. Issue 4 (30th December 2018) - Bevilacqua, Kristin; Schneider, Samantha; Rasul, Rehana; Taioli, Emanuela; Schwartz, Rebecca M.
Abstract: The Rockaways area of New York City was especially devastated by Hurricane Sandy. This study examined participant characteristics associated with acceptance of a linkage to and attendance at appointments for mental health difficulties (MHD). Participants (N = 1, 011) completed questionnaires to assess mental health symptoms. Participants who met screening criteria (n = 442) were offered linkage to care. Individuals who had a higher mental health symptom burden (MHSB; i.e., those who screened in on more than one criteria vs. only one criterion) had 2.68 greater odds of accepting services (95% confidence interval [1.68, 4.26]). MHSB was not associated with attending a first appointment (p = 0.80). Female gender and Hispanic ethnicity were also associated with acceptance of linkage to care, though not attendance. Reducing stigma around MHD associated with natural disasters and increasing knowledge about the mental health care system could promote help‐seeking behavior among survivors.